Personal and social factors involved in internet addiction among adolescents: A meta-analysis - Fumero, Ascensión; Marrero, Rosario J.; Voltes, Dolores; Peñate, Wenceslao (Computers in human behavior, 2018)
The growing popularity and frequency of Internet use has resulted in a large number of studies reporting various clinical problems associated with its abuse. The main purpose of this study is to conduct a meta-analysis of the association between Internet addiction (IA) and a number of personal and social psychological factors in adolescents. The search included cross-sectional, case-control and cohort studies which analyzed the relationship between IA and at least one of the following personal variables: (i) psychopathology, (ii) personality features and (iii) social difficulties, as well as (iv) self-esteem, (v) social skills and (vi) positive family functioning. These variables were classified as protective and promoting factors of the risk of developing IA. A total of 28 studies with adequate methodological quality were identified in the primary medical, health and psychological literature databases up to November 2017. Of the 48,090 students included in the analysis, 6548 (13.62%) were identified as excessive Internet users. The results highlight that risk factors had a greater effect on IA than protective factors. Also, personal factors showed a greater link with IA than social factors. The data provide relevant information for those developing programs for the prevention of IA and the enhancement of protective factors. •Internet addiction (IA) was associated with psychosocial factors in adolescents.•The risk factors had a greater effect on IA than protective factors.•Personal factors showed a greater association with IA than social factors.•Hostility, depression and anxiety showed the greatest link with IA.